Answer

Verified

339.6k+ views

**Hint:**Here, we are required to find the value of \[x - y\]. We would solve the given equations by any of the accepted methods and find the values of \[x\] and \[y\] respectively. Substituting their values in\[x - y\], we would get our required answer.

**Complete step-by-step answer:**

The given two equations are:

\[19x - 17y = 55\] ………..\[\left( 1 \right)\]

\[17x - 19y = 53\]………..\[\left( 2 \right)\]

We will multiply equation \[\left( 1 \right)\] by 17, we get

\[\left( {19x - 17y} \right) \times 17 = 55 \times 17\]

\[ \Rightarrow \left( {19 \times 17} \right)x - {17^2}y = 55 \times 17\]……………………….\[\left( 3 \right)\]

We will multiply equation \[\left( 2 \right)\] by 19, we get

\[\left( {17x - 19y} \right) \times 19 = 53 \times 19\]

\[ \Rightarrow \left( {17 \times 19} \right)x \times {19^2}y = 53 \times 19\]………………………\[\left( 4 \right)\]

Hence, subtracting the equations, we get,

Hence, subtracting the equation \[\left( 4 \right)\] from equation \[\left( 3 \right)\], we get,

\[\left[ {\left( {19 \times 17} \right)x - {{17}^2}y} \right] - \left[ {\left( {19 \times 17} \right)x - {{19}^2}y} \right] = 55 \times 17 - 53 \times 19\]

\[ \Rightarrow \left( {19 \times 17} \right)x - {17^2}y - \left( {19 \times 17} \right)x + {19^2}y = 55 \times 17 - 53 \times 19\]

Solving the terms with same variables, we get,

\[ \Rightarrow \left( {{{19}^2} - {{17}^2}} \right)y = \left( {55 \times 17} \right) - \left( {53 \times 19} \right)\]

Now, applying the identity \[\left( {{a^2} - {b^2}} \right) = \left( {a + b} \right)\left( {a - b} \right)\]

\[ \Rightarrow \left( {19 + 17} \right)\left( {19 - 17} \right)y = \left( {55 \times 17} \right) - \left( {53 \times 19} \right)\]

Now, we would transport everything which is multiplying to the variable \[y\] in the LHS to the denominator of RHS.

\[ \Rightarrow y = \dfrac{{\left( {55 \times 17} \right) - \left( {53 \times 19} \right)}}{{\left( {19 + 17} \right)\left( {19 - 17} \right)}}\]

Now, we would solve this further,

\[ \Rightarrow y = \dfrac{{935 - 1007}}{{36 \times 2}}\]

\[ \Rightarrow y = \dfrac{{ - 72}}{{72}}\]

\[ \Rightarrow y = - 1\]

Now, substituting this value in the equation,\[19x - 17y = 55\], we get,

\[19x - 17\left( { - 1} \right) = 55\]

\[19x + 17 = 55\]

Subtracting 17 from both sides,

\[19x = 38\]

Dividing both sides by 19

\[ \Rightarrow x = 2\]

Therefore, the required value of \[x - y\] is:

\[x - y = 2 - \left( { - 1} \right)\]

\[ \Rightarrow x - y = 2 + 1 = 3\]

Therefore, if \[19x - 17y = 55\] and \[17x - 19y = 53\], then the value of \[x - y = 3\]

**Hence, option C is the required answer.**

**Note:**

We can notice in the given two equations that the coefficient of \[x\] in the first equation is the coefficient of \[y\] in the second equation. Similarly, the coefficient of \[y\] in the first equation is the coefficient of \[x\] in the second equation.

Hence, there is another way to solve this question.

The given two equations are:

\[19x - 17y = 55\] ………..\[\left( 1 \right)\]

\[17x - 19y = 53\]………..\[\left( 2 \right)\]

Now, adding the equations \[\left( 1 \right)\] and \[\left( 2 \right)\], we get,

\[19x - 17y + 17x - 19y = 55 + 53\]

\[ \Rightarrow 36x - 36y = 108\]

Now, taking 36 common in the LHS,

\[ \Rightarrow 36\left( {x - y} \right) = 108\]

Dividing both sides by 36

\[ \Rightarrow x - y = 3\]…………………………\[\left( 5 \right)\]

Similarly, subtracting the equations \[\left( 1 \right)\] and \[\left( 2 \right)\], we get,

\[19x - 17y - 17x + 19y = 55 - 53\]

\[ \Rightarrow 2x + 2y = 2\]

Now, taking 2 common in the LHS,

\[ \Rightarrow 2\left( {x + y} \right) = 2\]

Dividing both sides by 2

\[ \Rightarrow x + y = 1\]…………………………\[\left( 6 \right)\]

Now, adding the equations \[\left( 5 \right)\] and \[\left( 6 \right)\] using elimination method,

\[ \Rightarrow x - y + x + y = 3 + 1\]

\[ \Rightarrow 2x = 4\]

Dividing both sides by 2, we get

\[ \Rightarrow x = 2\]

Substituting this value in equation \[\left( 5 \right)\]

\[ \Rightarrow x - y = 3\]

\[ \Rightarrow 2 - y = 3\]

\[ \Rightarrow y = 2 - 3 = - 1\]

Therefore, the required value of \[x - y\] is:

\[x - y = 2 - \left( { - 1} \right)\]

\[ \Rightarrow x - y = 2 + 1 = 3\]

Hence, we could attempt this question by either of the two ways.

Recently Updated Pages

The branch of science which deals with nature and natural class 10 physics CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Define absolute refractive index of a medium

Find out what do the algal bloom and redtides sign class 10 biology CBSE

Prove that the function fleft x right xn is continuous class 12 maths CBSE

Find the values of other five trigonometric functions class 10 maths CBSE

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Distinguish between the reserved forests and protected class 10 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give simple chemical tests to distinguish between the class 12 chemistry CBSE

Difference Between Plant Cell and Animal Cell

Which of the following books is not written by Harshavardhana class 6 social science CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

In which states of India are mango showers common What class 9 social science CBSE

What Made Mr Keesing Allow Anne to Talk in Class class 10 english CBSE